Health and social care educators’ experiences of their occupational well-being - Vauhkonen, Anneli; Rinne, Jenni; Salminen, Leena; Kähkönen, Outi; Saaranen, Terhi (Hoitotieteiden tutkimusseura HTTS r.y., 2026)
This cross-sectional study describes health and social care educators’ experiences of the four aspects of occupational well-being: working conditions, work community, worker’s resources and work, and professional competence. Data were collected in autumn 2020 by an electronic survey of which open ended questions are reported. Data were analysed using a deductive-inductive approach to content analysis and statistical descriptive methods for background information.
The occupational well-being promoting resources reported by educators (n=454) included meaningful work, social support, and sufficient professional competence. Workload factors reducing occupational well-being were unbalanced workload, inadequate organizational work planning, and challenges in the working atmosphere.
Good resources exist to address workload issues, and ongoing acknowledgment of these factors is crucial for fostering a supportive work community.